Толковый словарь живого великорусского языка - Даль Владимир Иванович (Бизнессофт, 2004)
Экземпляры: ЧЗ (20060608) / Инвентарный номер: 40807 / Цена: 140.00 / Сис.шифр: 81.2Рус.-4 40807 / Авт.знак: Д15 / ББК: 81.2Рус.-4